My little doctor's bag - " Bampton , Claire " (China : Parragon, 2005)
"My Little Doctor's Bag" is an interactive board book designed for young children, authored and illustrated by Nathan Reed. Shaped like a doctor's bag, it includes four removable play pieces$1 (Ba stethoscope, thermometer, syringe, and bandage$1 (Ballowing children to engage in imaginative play as they learn about the tools doctors use. Each page presents a different medical scenario, encouraging kids to use the appropriate instrument, thereby enhancing their understanding of basic medical equipment and fostering empathy through role-playing.s